COMPARATIVE MOLECULAR ANALYSIS OF ISSR MARKERS IN ARABIAN HORSE BREEDS - A. Sheikh; M. M. M. Ahmed; M. H. Z. Mutwakil; K. S. Saini; F. A.S. Alsulaimany; A. A EL Hanafy; J. S. M. Sabir (Journal of Animal and Plant Sciences, 2018)
Microsatellites are abundantly present in nuclear genome. They are renowned for their utility in polymorphism analyses. The informativeness of multilocus ISSR (Inter-simple sequence repeats) markers was compared to analyze the Arabian horse breeds (Equus caballus) including Middle Eastern Arabian (28) and mixed (hybrid) Arabians (10). They are helpful in the assessment of genetic diversity among horse populations. The marker (GA)9C gave 18 alleles in electrophoretic agarose gel. The low number of loci were detected with the (CA)9G ISSR marker. We calculated the Polymorphism Information Content (PIC) for each of the 12 ISSR markers. In total, 136 alleles were obtained with 12 ISSR markers. The allelic frequencies were also calculated which were ranging from 0.2 to 1.The PIC values were ranging 0.07 to 0.48 from lowest to highest respectively. Trinucleotide-based ISSR markers were found to be more conclusive than the dinucleotide ones. The overall average PIC was 0.2994. The polymorphic bands and their proportion were directly proportional to the PIC value. The highest PIC value detected with the trinucleotide marker (GTG)7C i.e.(0.48).
Keywords: Equus caballus; Inter simple sequence repeats; Genetic diversity; Polymorphism information content (PIC)